Reducing income transfers to refugee immigrants: does starthelp help you start? - Michael Rosholm; Rune M. Vejlin (Institute for the Study of Labor (IZA), 2007)
In this paper we estimate the causal effect of lowering the public income transfers administered to newly arrived refugee immigrants in Denmark - the so-called starthelp - using a competing risk mixed proportional hazard framework. The two competing risks are exit to job and exit out of the labour force. A standard search model predicts that lower benefits decrease the reservation wage and/or increase the search effort. However, newly arrived refugee immigrants may initially have a weak position in the labour market due to the fact that they do not know the language and typically have no education, or alternatively, their education is not recognized in Denmark. Hence, there may be no demand for their skills. The empirical question addressed here is whether lower benefits affect their job finding rate; if no employer wants to hire them at the going minimum wage, the fact that the reservation wage is lowered may have little effect. For identification we use a 'quasi-natural' experiment, in which the rules for welfare benefits in Denmark changed rather dramatically. Refugee immigrants obtaining residence permit before July 1st 2002 received and continue to receive larger income transfers than those obtaining their residence permit after July 1st. We find that lowering public income transfers has a small positive effect on the job finding rate, once calendar time effects are introduced into the model. However, introducing time-variation in the effect, we find that most of the positive effect stems from a large positive effect after two years in Denmark. We also find that the exit rate from the labour force is positively affected by lower transfers, but here the effect is large during the first year in the host country, and then it declines. Furthermore, we investigate heterogeneous treatment effects, and we find, generally, that those which we consider the weakest in the labour market are close to being immune to this treatment.
urn:nbn:de:101:1-20080402542
Keywords: 330; Flüchtlinge; Migranten; Sozialhilfe; Anspruchslohn; Arbeitsuche; Dänemark